A Fully Printable Hole‐Transporter‐Free Semi‐Transparent Perovskite Solar Cell. Issue 36 (15th September 2021) - Saleh, Amina; Pellet, Norman; Zakeeruddin, Shaik Mohammed; Dar, M. Ibrahim; Grätzel, Michael
Abstract: Perovskite solar cells (PSCs) have gained tremendous attention owing to their promising photovoltaic performance, surpassing all the alternative technologies based on solution‐processed materials. PSCs displaying record efficiencies contain hole transporting material (HTM) and gold back contact, which are too expensive for large‐scale deployment. Although the HTM‐free PSCs have been reported, a few can be used in tandem configuration, an architecture that is warranted to commercialize PSCs. This work presents, to the best of our knowledge, the first HTM‐free and Au‐free PSCs that are semi‐transparent in the IR region (desired for tandem cells) with an efficiency of 8.3 %. We systematically investigate the effect of varying the thickness of active and charge conducting layers on the photovoltaic performance of PSCs. Besides, semitransparency, another advantage of the scaffold is its simplicity: a fully printable mesoporous structure consisting of a TiO2 layer (400 nm), Al2 O3 as a separator layer (500 nm) and tin‐doped indium oxide (ITO) layer (5 μm), rendering our work highly pertinent for upscaling and large‐scale applications. Abstract : The first hole‐transport‐material‐free and Au‐free perovskite solar cell that is semi‐transparent in the IR for tandem cells is presented. Its mesoporous structure is fully printable and simple, and the effect of varying the thickness of each layer on the photovoltaic performance has been studied.